PENGARUH SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN PENGAWASAN KEUANGAN TERHADAP KUALITAS PELAPORAN KEUANGAN DAERAH - Pratiwi, Krismonika; Falah, Syaikhul; Blesia, Jhon U (Universitas Cenderawasih, 2023)
This study aims to analyze the effect of human resource capacity, utilization of Information Technology, and financial supervision on the quality of regional financial reporting in Yapen Islands regency. The quality of regional financial reporting is an important aspect in demonstrating transparency, accountability, and financial credibility of local governments. The research method uses a quantitative approach with data collection techniques through questionnaires. Respondents in this study is the financial SKPD Yapen Islands regency government totaling 49 people. The results of data analysis showed that human resource capacity has a significant influence on the quality of regional financial reporting. The more skilled, experienced, and trained human resources in the financial reporting process, the better the quality of reporting produced. However, the use of technology has no effect on the quality of regional financial reporting. Finally, financial supervision has also been shown to have a strong influence on the quality of regional financial reporting. When supervision is carried out Strictly and continuously, the potential for errors and fraud in reporting can be suppressed, so that the quality of reporting becomes better. Based on these findings, it is recommended that local governments pay more attention to improving human resource capacity through training and development, strengthening the use of Information Technology, and improving financial supervision systems to improve the quality of regional financial reporting. Thus, regional financial reporting will be more reliable, and people can have greater confidence in regional financial management.